Leadership as an Essential Graduate Attribute for Musicians - Reid, Anna; Bennett, Dawn; Rowley, Jennifer (Routledge, 2019)
This chapter draws on complexity theory to probe the theoretical and practical perspectives of leadership development and musician identities. It does so within the context of an internship programme designed to offer student musicians authentic workplace experiences. Complexity theory suggests that across multiple domains there are often three elements that enable the diverse situations to cohere. In this case, student musicians’ movement through multiple domains exposed three connective elements: namely, bridging the gap between theory and practice; flexibility; and reorienting learning as career relevance is realised. The inclusion of experiential learning in the education of professional musicians enabled the student musicians to develop essential, transferable skills such as leadership, communication, teamwork, workplace negotiation and problem-solving. Moreover, students learned to reimagine what their musical world might mean and how their own capabilities and creativity might come to the fore as leaders. This learning was evidenced in students’ reflections on this important professional experience. The skills identified by students are the same skills identified by recruiters and employers as vital to graduate transition, and the same skills identified by practising musicians as vital to leading complex careers within and beyond the music industry. The chapter reveals how students experience the liminal space between formal music study and internship work experiences and how, in turn, they transform their thinking from situation to situation.